Pertumbuhan dan Kandungan Calsium Tanaman Sawi dan Selada Hasil Biofortifikasi Mineral Calsium Secara Hidroponik - Munandar Munandar; Fitra Gustiar; Sekar Wahyu Ningsih; M. Ammar (xxxx-xxxx, 2020)
Munandar M, Gustiar F, Ningsih SW, Ammar M. 2020. Growth and calcium content of mustard and lettuce plants biofortificated with calcium grown hydroponically. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Mustard and lettuce are vegetables that can be a source of Ca. Efforts to increase the Ca plants can be done through biofortification, namely increasing the concentration of Ca through fertilizers in nutrient solution. However, excessive application of Ca is not recommended because it will be toxic to plants. This study aims to determine the effect of concentrations of Ca added to  AB Mix hydroponic solution  on Ca content, and growth of mustard (Brassica juncea L) and lettuce (Lactuca sativa L.). This study used a hydroponic water culture system, with a completely randomized design. Treatments of Ca concentration were: control, 100 ppm, 200 ppm, 300 ppm, and 400 ppm. The parameters observed were plant height, number of leaves, SPAD value, fresh and dry weight, and leaf Calcium concentration. The results showed (1) the addition of Ca 300 ppm into AB Mix solution was the optimal concentration for hydroponic biofortification of Ca in mustard and lettuce; (2) absorption of Ca nutrients increased the leaf number, SPAD value, and reduce the height of mustard and lettuce plants and (3) consumption of 100 grams of mustard and lettuce plants biofortificated with 300 ppm Ca can meet 41.6% and 24.8% of the daily requirement for calcium mineral, respectively. Application of Ca 300 ppm is the highest concentration of hydroponic nutrient solution which can increase the plant's Ca content without causing a biomass decrease.,  and